Productive Home Arrangement for Brick Processors Based on Community Empowerment (Case: South Bontolangkasa Village, Bontonompo Sub-district, Gowa Regency) - I Imriyanti (Architectural Research Journal, 2022)
The Brick processing in Bontolangkasa village, Bontonompo sub-district, Gowa district is very much so that the housing arrangement of the community is irregular. The use of the house as a residence as well as a business (productive house) so that there is a lack of a circulation system, the ventilation system to the dwelling is disturbed because of the heat from burning red bricks, irregular placement of traded red bricks. The solution to the problem of structuring the housing of the brick processing community in Bontolangkasa village, Bontonompo sub-district, Gowa district, requires community empowerment, namely providing information in data collection so that the drafting of the concept of structuring productive housing for the brick processing community can be implemented. The community service applied is the provision of information in the form of data that is compared to produce distances for the placement of brick processing systems in the residential area of the community. The arrangement of productive houses based on community empowerment in the brick processing houses of Bontolangkasa village is divided into 3 types of houses: stilt houses (balla rate'), stilt and modern houses (balla tingka') and modern houses (balla batu ), brick processing containers utilizing under the house and yard.